Aktualisasi Profil Guru Nahdlatul Ulama Inspiratif dalam Menghadapi Tantangan Revolusi Industri 4.0 - Sholihudin Al Ayubi; Wildah Nurul Islami (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2020)
Abstract: Inspirational teacher is a teacher who becomes a "mirror" for other teachers and has positive values ​​in themselves for students and the surrounding environment. Among the current problems of NU teachers is how to deal with the development of information and communication technology with an inspiring role. The formulation of the problem in this study is "What is the form of actualizing the profile of inspiring NU teachers in facing the industrial revolution 4.0?" This study aims to analyze the actualization of the profile of inspiring NU teachers in facing the challenges of the industrial revolution 4.0. This research is a qualitative research using a conceptual approach. Data collection methods using documentation and data analysis methods using qualitative descriptive analysis. The steps for actualizing the inspirational NU teacher profile include: 1. Examining the role of teachers and the challenges of the industrial revolution 4.0, 2. The importance of reflecting on the figure of KH. Hasyim Asy'ari was an inspiring figure of NU's ulama and teacher in the past but the results of his thoughts are still relevant to be applied in millennial times. Among the actualization forms of inspiring NU teacher profiles include three criteria namely ASWAJA's character, actively innovating, and actively literating.